EFEKTIVITAS PEMBELAJARAN MELALUI PENDEKATAN PROBLEM-CENTERED LEARNING PADA POKOK BAHASAN TEOREMA PYTHAGORAS - Melisa Mutiara Lestari Puloo; Abdul Wahab Abdullah; Tedy Machmud (Universitas Negeri Gorontalo, 2020)
This study aimed to describe the effectiveness of learned through the Problem-Centered Learning (PCL) approach on the Pythagorean Theorem subject. This study was quantitative descriptive. In this study, the effectiveness of learning through Problem-Centered Learning (PCL) approach on the subject of the Pythagorean Theorem based on teacher’s ability is managed learned through Problem-Centered Learning approach, student’s activities during learning through Problem-Centered Learning approach, student’s response after the following learning through Problem-Centered Learning approach, and student’s learned achievement. The data collection methods in this study were conducted through observation with observed sheets, tests, and questionnaires. The result of the research showed that learned through the Problem-Centered Learning approach on the Pythagorean Theorem subject was effective. This can be shown from Every aspect of the teacher’s ability to learn through the Problem-Centered Learning approach that satisfied the criteria of effectiveness with the good and very good category. Student’s activities through Problem-Centered Learning approach in learning were in the tolerance limit criteria so that categorization was effective. Student’s responses after implementation learned through the Problem-Centered Learning approach satisfied the criteria for effectiveness, with 87% of student's responses belonging in positive. Student learning achievement showed that satisfied minimum standard scored, 19 of 23 students or 82.61% got 2.75 scored or more.